Propuesta del Predimensionamiento de Instalaciones Sanitarias para la Villa Ecológica Finca La Cabaña en Remedios - Díaz Moya, Tatiana (Universidad Central "Marta Abreu" de las Villas, 2015)
The inadequacy and lack of sanitary facilities in the current functioning of the Curujey restaurant, located on the road between Remedios and Caibarien, preclude a good service at this facility Cubanacan. The need for capacity building of housing in the village Ecological Finca La Cabaña, where this restaurant, to respond to the increase in tourism is being experienced in the city of Remedios and in the program for the 500th anniversary of the city itself, he led the project to expand the services of the tourist facility in the Ecological Villa Finca La Cabaña driving the realization of ideas of pre-dimensioning of sanitary facilities and biogas ensuring comfort and functionality. Regulations and standards are reviewed and the proposed architectural design ideas of every work and general plan is studied in detail, it also makes a literature search and study of international and national repertoire as examples. Predimensionar requirements are proposed for sanitation and biogas as part of what may be the technical task that includes the study of history and location of the installation. Calculations for each item of work and the general plan are performed and results are obtained for architectural design ideas sanitation facilities each project complements the technical information. The specification is developed and through global economic indexes provide criteria also are illustrated and represent the results achieved with the design.
Keywords: Predimensionamiento de Instalaciones Sanitarias; Villa Ecológica Finca La Cabaña; Remedios; Restaurante el Curujey; Diseño Arquitectónico; Design; Sanitary Installations; Ecologic Region